Analysis of Bankruptcy Prediction in State-Owned Enter-prises in the Pharmaceuticals Sector - Santy Aji Sitohang; Wie Shi Wudjud; Efri Elsridayani Purba; Roris Tua Pandiangan; Yanuke Patricia Siahaan; Ramly Siahaan (International Forum of Researchers and Lecturers, 2025)
Operational performance of two state-owned pharmaceutical companies has been in the public spotlight in recent years. Poor financial conditions have caused both companies to experience net losses for years. The risk of bankruptcy becomes a serious threat if the fundamental problems of these two state-owned pharmaceutical companies are not successfully addressed. This study was conducted to determine whether PT. Kimia Farma Tbk and PT. Indofarma Tbk are likely to go bankrupt between 2021-2024 and to analyze the factors that could lead to bankruptcy. This study used a descriptive quantitative approach. Data were analyzed using Springate, Grover, and Zmijewski models to detect bankruptcy. Springate model predicted PT. Kimia Farma Tbk would be in the bankruptcy category from 2021-2024. Grover and Zmijewski model analysis showed that PT. Kimia Farma Tbk was in the healthy category from 2021-2022, then entered the bankruptcy category from 2023-2024. The potential for bankruptcy is influenced by poor liquidity, the company's reliance on debt to finance assets, unproductive asset management, and net losses. The condition of PT. Indofarma Tbk is categorized as bankrupt from 2021-2024 based on the Zmijewski and Springate models. The Grover model predicts PT. Indofarma Tbk will be healthy in 2021 and will then go bankrupt in 2022-2024. Indications of bankruptcy are influenced by declining sales and assets, debt exceeding assets, liquidity difficulties, and a continuing trend of losses.